Transport of isopropanol in H-ZSM5 by impedance spectroscopy - Nguyen, Tien Quang; Glorius, Maja; Breitkopf, Cornelia (Diffusion Fundamentals, 2016)
Gas diffusion mechanisms and diffusion coefficients in microkinetic system of solid materials characterize the different performance of chemical and transport processes. These factors should be evaluated with respect to the range of diffusion coefficients based on the number of experimental methods. Here, impedance spectroscopy which is a powerful tool for understanding transport phenomena of gases in nanostructured porous solids is used. In this work, we developed a new approach to compare and evaluate diffusion coefficients of isopropanol in the zeolite H-ZSM5. Furthermore, FTIR spectroscopy was used to study the adsorption of isopropanol in H-ZSM5 at different temperatures to support the interpretation of diffusion regimes. The combination of EIS with FTIR enables to illustrate preferred interaction sites and their influence on transport processes. The activation energy for transport of molecules in the channels is also calculated. Results are compared to literature data and suggest improved applications of EIS to characterize transport processes.